NILAI-NILAI PENDIDIKAN KARAKTER RELIGIUS DALAM BUKU DETONATOR KEBAIKAN KARYA DEWA EKA PRAYOGA - Moh Hafid Effendy; Nur Imamah; Mad Sa'i; Muliatul Maghfiroh (Journal of Education Partner, 2023)
This article aims to describe the manifestation of religious character education values ​​in the book Detonator of Kindness by Dewa Eka Prayoga, describe the meaning of the values ​​of religious character education in the book Detonator of Kindness by Dewa Eka Prayoga, describe the relevance of religious character education values ​​in the book Detonator of Kindness the work of Dewa Eka Prayoga with contemporary life. The approach used in this research is a qualitative research approach that is descriptive and analytical. This research is a type of library research. The data source used is the book Detonator of Kindness by Dewa Eka Prayoga, published by KMO Indonesia, Cirebon city in 2020. Data analysis uses content analysis or content study. The results of the research show that 1) There are forms of religious character education values ​​in the book Detonator of Kindness by Dewa Eka Prayoga, a) forms of life in the real world and, b) forms of life in the virtual world. 2) The meaning of the values ​​of religious character education in the book detonator of goodness by Dewa Eka Prayoga, namely: a) life in the real world is meaningful, praying for people, alms of wealth, taking lessons from an event, helping in goodness, learning religious knowledge, waqf Al-Qur'an, spread greetings to fellow Muslims, volunteer teachers, let go of debts, compete in goodness, be patient and grateful b) life in cyberspace is meaningful, share knowledge on social media, help on social media, and preach with social media.